# How do I solve for x, when 5x+3=-12

### 8 Answers | Add Yours

In an equation, both sides of the equal sign represent the same number, once all the math is done. An equals sign is like a see-saw: if an extra person gets on one side, then someone who weighs the same has to jump on the other side to keep the see-saw level. So you can add, subtract, multiply, or divide any number to one side of the equation as long as you do the exact same thing to the other side.

So, to solve for x in 5x + 3 = -12, we want to get x all alone on one side.

5x + 3 = -12

5x + 3 - 3 = -12 - 3 Subtract 3 from both sides

5x = -15 Simplify

5x/5 = -15/5 Divide both sides by 5

**x = -3**

Check the math:

5*(-3) + 3 =? -12

-15 + 3 =? -12

-12 = -12 check.

To solve 5x+3=-12:

An equation is like a balance .The position of the balance does not change if you add the same quantity to both sides.So also you can take away the same quantiy from both sides , the action does not alter the balance..You can multiply both sides by the same quantiy without alrering the balance. Also both sides can be divided by the same quantity by which the position of the balance does not change:

Subtract 3 from bothsides of the given equation:

5x+3**-3**=-12**-3**

5x=-15

Divide by 5 both sides

5x/**5**=-15/**5**

**x=-3** is the solution.

Tally :

Put **x=-3** in the original equation.

**LHS**: 5(**-3**)+3= -15+3=**-12**

**RHS:-12**

**Threfore, LHS =RHS.**

Talleyed. Hence our solution has passed the test.

How do I solve for x, when 5x+3=-12

In order to solve for x (variable) , we must isolate it.

5x + 3 = -12

5x + 3 -3 = -12 -3 (subtracting 3 from both sides)

5x = -15

5x/5 = -15/5 (dividing both sides by 5)

**x = -3 Answer.**

5x + 3 = -12 Subtract 3 from both sides of the equation. The 3 from the left side will be cancelled out so you will get...

3- (5x + 3) = (-12) -3

5x = -15 Now you will divide the 5 from 5x on both sides cancelling out the 5 in 5x which will get you the x by itself.

5/(5x) = (-15)/5

x = -3 Here is your answer!

5x + 3 = -12

You have to first get x alone by subtracting 3 from both of the sides

5x + 3 = -12

-3 -3

5x = -15

Divide both sides by 5

5x/5 = -15/5

After you divide the answer you should get is x = -3

5x + 3 = -12

First we have to try to get " x " alone, so subtract 3 on both sides

By subtracting, your equation should look like

**5x = -15 **now divide both sides by 5

By dividing, your equation should look like

**x = -3 **which is your answer

r x, when 5x+3=-12

5x + 3 = -12

-3 -3

5x = -15

`(5x) / 5 = -15/5 `

**x=-3**

5x+3=-12

Undo the addition first

5x = -12 - 3 = -15

Now the multiplication

x = -15/5 = -3